Electromagnetic wave absorbing performance of multiphase (SiC/HfC/C)/SiO2 nanocomposites with an unique microstructure. Issue 4 (April 2021) - Pang, Liang; Luo, Heng; Fan, Xiaomeng; Zhou, Wei; Chen, Pengju; Xiao, Peng; Wen, Qingbo; Li, Yang; Yu, Zhaoju; Riedel, Ralf
Abstract: Dielectric properties and electromagnetic (EM) wave absorbing performance of monolithic (SiC/HfC/C)/SiO2 nanocomposites (denoted as SHCOs) have been investigated in the X-band (8.2–12.4 GHz). The multiphase SHCOs are composed of insulating SiO2 and SiC/HfC/C nanocomposite fillers (SHC), which fillers composed of semiconducting β-SiC, conductive HfC-Carbon core-shell nanoparticles, and interconnected carbon nanoribbons. Dielectric response indicates that the increased SHC content results in an enhanced imaginary part of the permittivity and dielectric loss, leading to an improved EM absorbing performance. The unique microstructure with an EM wave-transparent SiO2 matrix is favorable for impedance matching and effective EM wave propagation. The enhanced interface polarization and conduction loss are considered as the key mechanisms for EM wave attenuation. The minimum reflection loss of the SHCOs achieves – 60.7 dB containing 20 vol% of SHC (at 9.98 GHz) with the sample thickness of 3.33 mm, and the effective absorbing bandwidth (EAB) covers ca. 72 % of the X-band. The monolithic (SiC/HfC/C)/SiO2 nanocomposites with outstanding EM wave absorbing performance are promising candidates for EM application at high temperatures.